Exploring food waste behaviour during dining out at restaurants: Young consumers’ intention as a mediator - Rahmatika Mega Fitria; Fauzan Romadlon; Siti Laksi Nurazizah (Indonesian Journal of Applied Environmental Studies, 2026)
Food waste is a global issue with significant social, economic, and environmental implications. Food waste can lead to environmental problems, including the release of greenhouse gases, global warming, and pollution. Food waste also affects society, as 800 million people experience hunger or malnutrition every year. Banyumas Regency, Indonesia, is one of the regencies that generates high food waste. One of the leading causes of food waste is post-consumer waste resulting from eating at restaurants or dining out. This study aims to analyze the influence of dining out behavior on food waste among young consumers in Banyumas Regency. The study examines dining-out behavior by identifying factors that contribute to food waste during dining out and exploring alternatives to mitigate its impact. The method employed was quantitative, involving interviews with 401 respondents. The data were analyzed using SEM-PLS. The results show that food choice (FC) has a significant influence on intention to reduce food waste (IFW), IFW has a significant influence on food waste behavior (FWB), and IFW mediates the relationship between FC and FWB. Furthermore, restaurants in Banyumas Regency can offer multiple portion sizes to young consumers, thereby reducing food waste. They can also provide a service to repackage leftovers made by consumers.